Citizen Opinion Survey: How a Mid-Sized California Community Perceives their Police Department - Chintakrindi, Sriram (2018)
Successful community policing is, in part, dependent on the community’s perception of their police officers. The police department of a mid-sized community in California’s Central Valley conducted a survey to gain some measure of the citizen’s perception of their police. The survey was conducted in conjunction with a nearby California State University. The results of the survey are being used to make revisions in the policies and procedures of the police department. It also proved to be an interesting activity for the professors and students of the university